DISTRIBUSI HORIZONTAL MOLUSKA DI KAWASAN PADANG LAMUN PANTAI MERTA SEGARA SANUR, DENPASAR - Istiqlal, Buya Azmedia; Yusup, Deny Suhernawan; Suartini, Ni Made (Jurnal Biologi Udayana; Vol 17 No 1 (2013): Jurnal Biologi, 2013)
A research on spatial distribution of Mollusc inhabitant seagrass bed at Merta Segara Beach Sanur, Denpasar was carried out from October to December 2012. The study site is well recognized as a place of tourist activities. Line transects with quadrate methods were applied as the sampling technique. Samples were collected in a total of 60 quadrates (10 m x 2.5 m) from four line transects with the interval of 50 m between each transect. At a sampling point chosen randomly, one transect was lined up toward the sea, then on each side of transect, 15 quadrates were laid with the interval of 20 m. The study found 31 individuals which 24 were classified as Gastropods, and 7 individuals classified as Bivalve. Overall, the study indicated that the Mollusc communities were in stable condition (H’= 3,74 and E= 0,75). The horizontal distribution of Mollusc was neither associated with seagrass percentage cover or the use of jetty piling. The spatial distribution seemed related to the use of area as tourist activities.
Keywords: horizontal distribution, Mollusc, seagrass bed, Bali.